Microenvironment-Dependent Gradient of CTL Exhaustion in the AE17sOVA Murine Mesothelioma Tumor Model - Hope, Jennifer L.; Spantidea, Panagiota I.; Kiernan, Caoimhe H.; Stairiker, Christopher J.; Rijsbergen, Laurine C.; van Meurs, Marjan; Brouwers-Haspels, Inge; Mueller, Yvonne M.; Nelson, Delia J.; Bradley, Linda M.; Aerts, Joachim G. J. V.; Katsikis, Peter D. (Frontiers in Immunology, 2020)
The immune system, and in particular, cytotoxic CD8+ T cells (CTLs), plays a vital part in the prevention and elimination of tumors. In many patients, however, CTL-mediated tumor killing ultimately fails in the clearance of cancer cells resulting in disease progression, in large part due to the progression of effector CTL into exhausted CTL. While there have been major breakthroughs in the development of CTL-mediated “reinvigoration”-driven immunotherapies such as checkpoint blockade therapy, there remains a need to better understand the drivers behind the development of T cell exhaustion. Our study highlights the unique differences in T cell exhaustion development in tumor-specific CTL which arises over time in a mouse model of mesothelioma. Importantly, we also show that peripheral tumor-specific T cells have a unique expression profile compared to exhausted tumor-infiltrating CTL at a late-stage of tumor progression in mice. Together, these data suggest that greater emphasis should be placed on understanding contributions of individual microenvironments in the development of T cell exhaustion.